Growth and Survival Variation among Scots Pine (Pinus sylvestris L.) Provenances. (4th January 2017) - Gülcü, Süleyman; Bilir, Nebi
Abstract : Tree height, basal diameter, and survival were examined in thirteen-year-old provenance test established by 30 seed sources of Scots pine ( Pinus sylvestris L.) at two exotic sites of the species in Southern part of Turkey. Variations within provenance and among provenances and relations among the traits were estimated to compare Scots pine provenance and two other native species. Averages of tree height and basal diameter were 350 cm and 52.7 mm in Aydogmus site and 385 cm and 51.2 mm in Kemer site, respectively. There were large differences within and among provenances for the characters. Sites were similar (p > 0.05 ) for the characters, while there were significant differences (p ≤ 0.05 ) among provenances within site according to results of variance analysis (ANOVA). Scots pine provenances were higher and had more thickness than that of black pine ( Pinus nigra Arnold) and Taurus cedar ( Cedrus libani A. Rich.) which were natural species of the region. There were positive and significant (p < 0.05 ) correlations between height and basal diameter in the species. Average survivals were 56% and 35% of the provenances in the sites. They were 71% and 11% in black pine and 53% in Taurus cedar for the sites respectively.